Facile Fabrication of Lignin‐Cellulose Green Nanogels. Issue 21 (8th September 2022) - Sathasivam, Thenapakiam; Hu, Lixuan; Sugiarto, Sigit; Dou, Qingqing; Zhang, Zheng; Ru Tan, Hui; Leow, Yihao; Zhu, Qiang; Ken Lee, Chi‐Lik; Yu, Hai‐Dong; Kai, Dan
Abstract: There has been increasing exploration of the development and production of biodegradable polymers in response to issues with petrol‐based polymers and their impact on the environment. Here we report a new approach to synthesize a natural nanogel from lignin and nanocellulose. First, lignin nanobeads were synthesized by a solvent‐shifting method, which showed a spherical shape with a diameter of 159.7 nm. Then the lignin nanobeads were incorporated into a nanocellulose network to form the lignin/cellulose nanogels. The nanocellulose fibrils (CNF−C) nanogels reveal a higher storage modulus than the nanocellulose crystal (CNC−C) ones due to the denser network with self‐entanglement of longer cellulose chains. The presence of lignin nanobeads in the nanogels helped to increase the viscoelasticity of the nanogels. This work highlights that the new kinds of green nanogels could be potentially utilized in a variety of biomedical applications such as drug delivery and wound dressing. Abstract : This work reports the production of a nanogel utilizing natural polymers derived from lignocellulosic biomass (nanocellulose & nanolignin) in a simple one‐pot synthesis for potential biomedical or other value‐added applications.